PENGARUH FITUR LAYANAN DAN KEMUDAHAN TERHADAP MINAT MENGGUNAKAN BSI MOBILE PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Dea Fitria; Eja Armaz Hardi; Agusriandi Agusriandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The development of information technology has changed the way customers think about conducting banking transactions, where they prioritize ease, flexibility, efficiency, and simplicity. Mobile banking is one of the services provided by banks to enable customers to carry out their banking activities at any time without having to visit the bank in person. The aim of this research is to determine the effect of service features and ease of use on the interest in using BSI Mobile among students of the Faculty of Islamic Economics and Business at Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi.This research uses a quantitative approach. The population of the study consists of 336 respondents, and a random sampling technique was employed, selecting participants based on the region of the research object. The data analysis technique used to answer the research questions is multiple linear regression analysis using the SPSS program.The t-test results indicate that the service feature variable has a t-value greater than the t-table, specifically 190.629 > 3.02, meaning Ha is accepted and Ho is rejected. This implies that there is a significant effect of service features on interest. Similarly, the ease of use variable has a t-value greater than the t-table, specifically 4.421 > 1.967, meaning Ho1 is accepted and Ho2 is rejected. This shows that ease of use significantly influences the interest in using BSI Mobile.